2016
DOI: 10.1002/jmv.24725
|View full text |Cite
|
Sign up to set email alerts
|

National trends of hepatitis B and C during pregnancy across sociodemographic, behavioral, and clinical factors, United States, 1998–2011

Abstract: Currently, data examining nationally representative prevalence and trends of HBV or HCV among specific subgroups of pregnant women in the US are unavailable. We conducted a cross-sectional analysis of hospitalizations for liveborn singleton deliveries from 1998 to 2011 using data from the Nationwide Inpatient Sample. After identifying deliveries with HBV, HCV, and HIV infection during pregnancy, survey logistic regression was used to identify risk factors. Temporal trends were analyzed using joinpoint regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Two studies have estimated that between 10–17 of 100,000 pregnant women are chronically infected with HCV (Ellington, Flowers, Legardy-Williams, Jamieson, & Kourtis, 2015; Salihu et al, 2012). However, a recent retrospective study of inpatient pregnancies in the U.S. between 1998 and 2011, showed that HCV rates per 100,000 deliveries increased by over 5-fold, from 42 to 210 in those years, respectively (Salemi et al, 2016). Given this significant increase, it’s evident that HCV infection is rising in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have estimated that between 10–17 of 100,000 pregnant women are chronically infected with HCV (Ellington, Flowers, Legardy-Williams, Jamieson, & Kourtis, 2015; Salihu et al, 2012). However, a recent retrospective study of inpatient pregnancies in the U.S. between 1998 and 2011, showed that HCV rates per 100,000 deliveries increased by over 5-fold, from 42 to 210 in those years, respectively (Salemi et al, 2016). Given this significant increase, it’s evident that HCV infection is rising in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is most clearly defined in regards to coinfection with HIV and HCV. Mothers 19 Four of the included studies identified HIV infection as a risk factor for HCV. 17,19,22,23 An additional two studies found an association between history of any sexually transmitted infection and HCV.…”
Section: Risk Factors Of Hepatitis C Virus In Pregnancymentioning
confidence: 99%
“…(17) In the United States, the prevalence of infants born to HCV-infected mothers ranges from 0.5% in Ohio (18) to 2.3% in West Virginia, (19) with a 68% increase in infants born to HCV-infected women nationally, disproportionately higher than that in HBV or HIV. (20) Overall, there has been a 39% increase in HCV-positive pregnant women and 13% increase in HCV-positive children reported between 2011 and 2016. This may in part be due to increased testing, but it highlights the continued role of perinatal HCV transmission.…”
Section: Prevalence Of Hcv Infection In Women Of Reproductive Age Andmentioning
confidence: 99%